High hydrostatic pressure treatment improves physicochemical properties of calcium- and soybean protein-added peach juice - Manassero, Carlos Alberto (2018)
Calcium- and soybean proteins-added peach beverages were prepared and subjected to high hydrostatic pressure (HHP, 600 MPa, 5 min) in order to evaluate their physicochemical properties (protein solubility, physical stability, viscosity and color). Calcium addition decreased protein solubility and destabilized the beverage. Solubilizing effect of HHP was detected only for non-calcium-added beverages. Nevertheless, HHP treatment stabilized calcium-added beverages, with a greater effect in samples with 10 mmol L−1 CaCl2. HHP treatment increased viscosity of calcium-added beverages, which could contribute to their increase in physical stability. This work provides information that may be useful in the handling of functional foods, since physicochemical properties such as physical stability was improved by HHP in a drink with improved nutritional value (incorporation of proteins and calcium).